Labels of origin for food [ local development, global recognition - Barham, Elizabeth; Sylvander, Bertil (CABI, 2011)
This book seeks to set geographical indications (GIs) in the context of the overall development of today's economies and societies as marked by globalization and the interaction of cultures that this entails. The book is divided into two parts. The fir part (chapters 1-6) sets out the findings of a decade of research into GIs in Europe in the global context. The second part (chapters 7-10) is based on the existence of GIs as a sector in itself in the context of globalization. Included in the appendixes are GI case studies in Europe and maps of protected designations of origin and geographical indications (PDOs and PGIs). Also included are a glossary and a subject index.